Dinâmica populacional de ácaros (Acari) em clones de seringueira (Hevea brasiliensis Muell. Arg.) - Rezende, Joyce Martins (2015)
The rubber tree is native from Amazonia and belongs to Family Euphorbiaceae. The phytophagous mites are one of major pest problem found in rubber trees in Brazil, however, to ensure the sustainability of culture is necessary to access the seasonal occurrence of these mites. Moreover, no data on mites’ population dynamics at state of Goiás are available until now. Thus, in this study was evaluated the population dynamics of mites on XX rubber tree clones RRIM 600, PR 255, PB 235 e GT 1 at Goianésia city, Goiás State, Brazil. Therefore, assessments were performed fortnightly between June 2013 and June 2014. We evaluated the number of mites in seven leaves per tree, in a total of ten trees per clones in each sample. We analyzed two leaflets of each leaf under stereoscopic microscope, being central leaflet, designed for counting of the main phytophagous (Calacarus heveae and Tenuipalpus heveae) and another one lateral leaflet for sample other mites species. After the senescence, we observed occurrence of C. heveae and T. heveae. The C. heveae peak occurred between April and May in all clones. The PR 255 and RRIM 600 clones had higher rates of C. heveae individuals. On the other hand, GT 1 clone showed the lowest C. heveae population. During the study period was verified low population of T. heveae in all rubber tree clones, which presented its population peaks from November to December and from April to May. For other mite species, we recorded the predator Euseius citrifolius as the most abundant species, followed by the phytophagous Eutetranychus banksi and Oligonychus sp. The smaller population of microácaro in GT 1 clone may be related to the high number of predatory mites and because of the existing secondary compounds in the plant. The RRIM 600 clone showed susceptibility to C. heveae, and was the clone, which obtained the lowest abundance of predators. The PR 255 clone was considered highly susceptible to the development of the eriophyid mite. These results are relevant to the management of C. heveae on the rubber tree crops.